On the Magnetosphere‐Ionosphere Coupling During the May 2021 Geomagnetic Storm. Issue 6 (6th June 2022) - Piersanti, M.; Del Moro, D.; Parmentier, A.; Martucci, M.; Palma, F.; Sotgiu, A.; Plainaki, C.; D'Angelo, G.; Berrilli, F.; Recchiuti, D.; Papini, E.; Giovannelli, L.; et al.
Abstract: On 12 May 2021 the interplanetary doppelgänger of the 9 May 2021 coronal mass ejection impacted the Earth's magnetosphere, giving rise to a strong geomagnetic storm. This paper discusses the evolution of the various events linking the solar activity to the Earth's ionosphere with special focus on the effects observed in the circumterrestrial environment. We investigate the propagation of the interplanetary coronal mass ejection and its interaction with the magnetosphere—ionosphere system in terms of both magnetospheric current systems and particle redistribution, by jointly analyzing data from interplanetary, magnetospheric, and low Earth orbiting satellites. The principal magnetospheric current system activated during the different phases of the geomagnetic storm was correctly identified through the direct comparison between geosynchronous orbit observations and model predictions. From the particle point of view, we have found that the primary impact of the storm development is a net and rapid loss of relativistic electrons from the entire outer radiation belt. Our analysis shows no evidence for any short‐term recovery to pre‐storm levels during the days following the main phase. Storm effects also included a small Forbush decrease driven by the interplay between the interplanetary shock and subsequent magnetic cloud arrival. Plain Language Summary: On 12 May 2021 a coronal mass ejection (CME) emitted from the Sun on 9 May 2021 impacted the Earth, giving rise to a strong geomagnetic storm. This paper present a global view of the CME effects observed in the circumterrestrial environment focusing on its propagation and on its interaction with the magnetosphere—ionosphere system in terms of both magnetospheric current systems and particle redistribution, by jointly analyzing data from interplanetary, magnetospheric, and low Earth orbiting satellites. The principal magnetospheric current system activated during the different phases of the geomagnetic storm was correctly identified through the direct comparison between geosynchronous orbit observations and model predictions. From the particle point of view, we have found that the primary impact of the storm development is a sudden loss of relativistic electrons from the entire outer radiation belt. Such kind of a global analysis is still the straightforward way available to understand the complex dynamics of the processes occurring in the circumterrestrial environment from a space weather point of view. Key Points: Global analysis of the 12 May 2021 geomagnetic storm Interplanetary coronal mass ejections propagation in the interplanetary space Magnetospheric‐ionospheric coupling analysis from both particle and field point of view